2024
DOI: 10.1101/2024.02.12.579763
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deciphering Peptide-Protein Interactions via Composition-Based Prediction: A Case Study with Survivin/BIRC5

Atsarina Larasati Anindya,
Torbjörn Nur Olsson,
Maja Jensen
et al.

Abstract: In the realm of atomic physics and chemistry, composition emerges as the most powerful means of describing matter. Mendeleev’s periodic table and chemical formulas, while not entirely free from ambiguities, provide robust approximations for comprehending the properties of atoms, chemicals, and their collective behaviours, which stem from the dynamic interplay of their constituents.Our study illustrates that protein-protein interactions follow a similar paradigm, wherein the composition of peptides plays a pivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 93 publications
(136 reference statements)
0
3
0
Order By: Relevance
“…To investigate in detail the interaction between survivin and the BAF complex, we applied the compositional analysis of proteins comprising the conventional (c)BAF and polybromo(P)BAF complexes aiming to predict their interaction with survivin. For this purpose, we utilized the peptide model based on the functional group composition of each protein of the complex (Jensen et al, 2023; Anindya et al, 2024). We identified that SMARCD1, SMARCA2, SMARCA4, SMARCC1, and BRD7 exhibit comparable ratios between the predicted binding peptides to the total number of generated peptides (R bind ) values in the range of 0.39-0.43.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate in detail the interaction between survivin and the BAF complex, we applied the compositional analysis of proteins comprising the conventional (c)BAF and polybromo(P)BAF complexes aiming to predict their interaction with survivin. For this purpose, we utilized the peptide model based on the functional group composition of each protein of the complex (Jensen et al, 2023; Anindya et al, 2024). We identified that SMARCD1, SMARCA2, SMARCA4, SMARCC1, and BRD7 exhibit comparable ratios between the predicted binding peptides to the total number of generated peptides (R bind ) values in the range of 0.39-0.43.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the functional composition of the protein, defined by the presence of atomic groups (C, CH, CH 2 , CH 3 , hydroxyl, phenyl, carboxyl, amide, sulfhydryl, etc.) rather than the sequence of amino acids, we develop a strategy for predicting fitness of a given protein/peptide to survivin in biological and a chemical context (Jensen et al, 2023; Anindya et al, 2024) with the following adjustments. The multilayer perceptron classifier comprised two intermediate layer neurons, and C-Pos encoding was employed to interpret 15 amino acid-long peptides.…”
Section: Methodsmentioning
confidence: 99%
“…Concerning the biological function of these groups, there has been speculation about which properties of peptides are crucial in determining their interaction with promiscuous proteins such as survivin. In this example, it appears that the sequence does not provide substantially more deterministic power compared to composition 62,63 . However, for an effective model, the composition must include a detailed description of functional groups in the amino acids, rather than simply considering the number of hydrophobic and hydrophilic amino acids, net charge, and charge density.…”
Section: Atom Fluctuations (B-factors) In a Squeezing Processmentioning
confidence: 91%